Penghapusan Merek WIN Terdaftar yang Tidak Digunakan dalam Kegiatan Perdagangan Berdasarkan Kepentingan Pihak Ketiga : Studi Kasus Putusan Pengadilan Niaga Jakarta Pusat Nomor 45/Pdt.Sus-HKI/Merek/2023/PN.Niaga.Jkt.Pst - Azizah Arfah; Angel Evelin; Hendra Parulian; Maulida Fitriani; Rildo Anuar Sihite; Handoyo Prasetyo; Atik Winanti (STIKes Ibnu Sina Ajibarang, 2025)
The right holder of a trademark has full validity to use his own trademark or license it to other parties, including delisting of its own trademark. Delisting of a mark could be done by the owner of the relevant mark, based on initiative of the minister or third party’s interest. Hongyunhonghe Tobacco (Group) Co. Ltd. (Plaintiff) has filed a lawsuit for the delisting of registered WIN trademark owned by PT Sumatra Tobacco Trading Company (Defendant). The issues raised are how the legal arrangements for the delisting of trademarks by third party’s interested and the suitability of the application of the law in Decision Number 45/Pdt.Sus-HKI/Merek/2023/PN.Niaga.Jkt.Pstreviewed based on the applicable trademark rules. Normative juridical research type through a statutory study approach and literature study-based data collection. Qualitative data analysis with prescriptive nature. The provisions of Article 74 paragraph (1) jo. Article 85 of the Trademark Law regulates the delisting of registered trademarks filed third party’s interested in the form of a lawsuit to the Chairman of the Central Jakarta Commercial Court. The application of the law applied in the decision is erroneous and states the Plaintiff is not interested. Law enforcement is one of the factors that affect the effectiveness and utilities of the law for the community. Trademarks that have been obtained should be used as well as possible in accordance with the term of protection, so as not to cause a gap for other parties to conduct the delisting of registered trademarks.